Implementation of the readathon program and library socialization to enhance critical thinking skills, reading comprehension, and literacy of students at SMP Negeri 34 - Yudisman, Septevan Nanda; Jalinur, Jalinur; Iman, Ramdhani Nur (INDONESIAN JOURNAL OF SUSTAINABILITY, 2025)
This study aims to evaluate the effectiveness of the Readathon Program and library socialization in enhancing critical thinking skills and reading comprehension among students at SMP Negeri 34 Kota Bekasi. Reading is a fundamental skill essential for learning and developing students' critical thinking abilities. According to Anisa et al. (2021), "a lack of literacy can hinder students' critical thinking skills." Therefore, programs that involve libraries as learning centers are necessary to increase students' reading interest. The research method employed a quantitative descriptive approach, involving 1,041 students from grades VII to IX, with a random sample of 270 students. Data collection was conducted through questionnaires, interviews, and tests to measure reading comprehension and critical thinking skills before and after the program was implemented. Statistical analysis used paired t-tests to examine the significance of score changes. The results showed that the average reading comprehension score increased from 65.4 to 78.9, and critical thinking skills improved from 61.3 to 75.7 after the program. The paired t-test indicated a significant increase at p < 0.05. Thus, the Readathon Program and library socialization proved effective in enhancing students' literacy. In conclusion, this study emphasizes the importance of developing engaging literacy programs that involve libraries as learning centers. Schools are encouraged to continue developing literacy activities to foster a strong literacy culture within the school environment.